2021
DOI: 10.1186/s13034-021-00413-2
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between mobile phone addiction and coping style among Chinese adolescents: a meta-analysis

Abstract: Background Mobile phone addiction has become a social problem that affects the healthy growth of adolescents, and it may be correlated with coping style. The aim of this study was to investigate the relationship between mobile phone addiction and coping style and the influencing factors for adolescents. Methods A meta-analysis was conducted by searching China National Knowledge Infrastructure (CNKI), WANFANG DATA and Chongqing VIP Information Co., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…An increasing amount of evidence has shown that SA not only causes a series of mental health problems, such as anxiety and depression ( Coyne et al, 2020 ), but also damages the physical health of individuals, resulting in visual fatigue, reduced immunity, and sleep disorders ( Liu Q. Q. et al, 2017 ). Simultaneously, it also causes individual cognitive failure ( Hong et al, 2020 ) and has a negative impact on academic achievement, coping styles, and family and other interpersonal relationships ( Clayton et al, 2015 ; Nayak, 2018 ; Lu et al, 2021 ). According to mental health experts, SA will become one of the most important behavioral addictions of the twenty-first century ( Chóliz, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence has shown that SA not only causes a series of mental health problems, such as anxiety and depression ( Coyne et al, 2020 ), but also damages the physical health of individuals, resulting in visual fatigue, reduced immunity, and sleep disorders ( Liu Q. Q. et al, 2017 ). Simultaneously, it also causes individual cognitive failure ( Hong et al, 2020 ) and has a negative impact on academic achievement, coping styles, and family and other interpersonal relationships ( Clayton et al, 2015 ; Nayak, 2018 ; Lu et al, 2021 ). According to mental health experts, SA will become one of the most important behavioral addictions of the twenty-first century ( Chóliz, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, smartphone addiction has become a social problem that affects the healthy growth of adolescents. A large number of studies have found that smartphone addiction not only confers psychological and physiological effects on adolescents (e.g., anxiety, depression, and stress) but also negatively affects academic performance, coping styles, interpersonal relationships, etc., (Clayton et al, 2015 ; Samaha and Hawi, 2016 ; Lu et al, 2021 ; Diotaiuti et al, 2022 ; Wang et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ). Adolescents are in an important stage of developing peer relationships, pursuing autonomy and individuality, and changing behavior (Laursen and Hartl, 2013 ; Mak et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Improved psychological resilience will reduce mobile phone addiction risk. The Simplified Coping Style Questionnaire (SCSQ) revealed that coping style had a robust effect on adolescent mobile phone addiction ( Lu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Improved psychological resilience will reduce mobile phone addiction risk. The Simplified Coping Style Questionnaire (SCSQ) revealed that coping style had a robust effect on adolescent mobile phone addiction (Lu et al, 2021). Depression, anxiety, and stress could moderate the relationship between adolescent psychological resilience and mobile phone addiction.…”
Section: Mediated Rolementioning
confidence: 99%